Near field communication enabled mobile payments: preliminary study - Brohi, Imtiaz Ali; Imtiaz Ali, Najma; Shah, Asadullah; S. Abd. Aziz, Madihah; Mohd. Tamrin, Mohd. Izzuddin (Science Publishing Corporation Inc, 2018)
The ubiquitous computing has made consumers life easy, it has given the new way to interact with family and friends and perform many activities which were impossible in previous time. One of the profound achievement of ubiquitous computing is Mobile Payment and an advanced mode of the mobile payment is the near field communication mobile payment. In this study the authors have proposed theoreti-cal near field communication mobile payment model that is based on extended unified technology acceptance and use of technology (UTAUT2) .In this paper, the author have performed the pilot study to validate the variables and to verify their reliability among the proposed items. The results has proven that there is a reliability among the items in variables, as the Cronbach’s alpha value for the vari-ables is above or equal to 0.7.